Incident ischaemic stroke and Type 2 diabetes: trends in incidence and case fatality in Scotland 2004–2013. Issue 1 (6th November 2017) - Read, S. H.; McAllister, D. A.; Colhoun, H. M.; Farran, B.; Fischbacher, C.; Kerssens, J. J.; Leese, G. P.; Lindsay, R. S.; McCrimmon, R. J.; McGurnaghan, S.; Philip, S.; Sattar, N.; et al.
Abstract: Aim: To describe trends in first ischaemic stroke incidence and case fatality in adults with and without a diagnosis of Type 2 diabetes prior to their ischaemic stroke event in Scotland between 2004 and 2013. Methods: Using population‐wide hospital admission, death and diabetes datasets, we conducted a retrospective cohort study. Negative binomial and logistic regression models were used to calculate year‐specific incidence and case‐fatality rates for people with Type 2 diabetes and for people without diabetes. Results: During 41.0 million person‐years of follow‐up there were 69 757 ischaemic stroke events. Type 2 diabetes prevalence among patients who experienced ischaemic stroke increased from 13.5% to 20.3% between 2004 and 2013. Stroke incidence rates declined by 2.7% (95% CI 2.4, 3.0) annually for people with and without diabetes [diabetes/year interaction: rate ratio 0.99 (95% CI 0.98, 1.01)]. Type 2 diabetes was associated with an increased risk of ischaemic stroke in men [rate ratio 1.23 (95% CI 1.17, 1.30)] and women [rate ratio 1.41 (95% CI 1.35, 1.48)]. Case‐fatality rates were 14.2% and 12.7% in people with Type 2 diabetes and without diabetes, respectively. Case fatality declined by 3.5% (95% CI 2.7, 4.5) annually [diabetes/year interaction: odds ratio 1.01 (95% CI 0.98, 1.02)]. Conclusions: Ischaemic stroke incidence declined no faster in people with a diagnosis of Type 2 diabetes than in people without diabetes. Increasing prevalence of Type 2 diabetes among stroke patients may mean that declines in case fatality over time will be less marked in the future. What's new?: Using population‐wide registers we describe contemporary trends in ischaemic stroke incidence and case fatality in people with and without a diagnosis of Type 2 diabetes. Declines in ischaemic stroke incidence and case fatality have occurred at the same rate in people with and without a diagnosis of Type 2 diabetes, despite attempts to intensify cardiovascular disease risk factor control in people with diabetes. Between 2004 and 2013, the prevalence of Type 2 diabetes in patients experiencing ischaemic stroke in Scotland increased from 13.5% to 20.3%.